Integrative Learning in Award-Winning Student Writing: A Grounded Theory Analysis - Ethan Youngerman (SAGE Publishing, 2018)
Integrative learning is a cognitive outcome that reveals students making intellectual connections, bringing sources together, and integrating them into one. What are the kinds of sources integrated by students in writing, and what are the categories or forms that characterize those integrations? How are the sources integrated by students in writing, and what are the strategies, habits of mind, or processes that characterize those integrations? I analyzed 32 student essays using grounded theory. Three categories of what students integrate emerged: two sources, multiple sources, and metacognitive sources. Such sources ranged from published texts to personal experiences. How students integrate also fell into three categories: connection, application, and synthesis. Students integrate through connections via equivalencies, contrasts, bridges, and intellectual problems. Applications may apply an idea to the "real world" or one source to another. Synthesis often takes the form of idea, judgment, gathering, and/or implications. A revised empirical definition of integrative learning emerged from the typologies of what and how students integrate.